A NEW MANGROVE ASSOCIATED SPECIES RECORD (CONOCARPUS L. -COMBRETACEAE) FROM TAMIL NADU - Dhaarani, Vijayakumar; Sarvalingam, Ariyan; Rajendran, Arumugam (Current Botany, 2018)
Abstract: The genus Conocarpus L., (Combrataceae) a naturalized mangrove genus of India, is reported as an addition to the flora of Tamil Nadu. The species Conocarpus erectus L., was known to occur in Western Africa, Tropical and Subtropical America. A detailed description along with details on habitat, distribution and photographs and related genus key is provided here.